Incazelo nomthelela ekuhlalisaneni kwabantu evezwa ekwethiweni kwamagama emizi yeNkosi uMzilikazi - Khumalo, Dumisani Ephraim (My University, 2019)
This research study investigates the aetiology in King Mzilikazi’s homestead names and the influence of homestead naming to the social dynamics. The researcher highlighted the view that King Mzilikazi used to bestow his homestead names with an intention to send a message to the people he was associated with as well as his enemies. The research applied the qualitative approach in search of the information and views presented by different participants in the study. Hermeneutics theory and Semantics theory by Nicholaisen were employed with an attempt to interpret the findings as presented b different participants views. The research results presented the relationship between the assigning of regiments names to the names escalation to a point where they are used as homestead names. The research also highlighted the angle of homestead names which escalated further the be recognised as place names of which some of them are still active even today. The research also presented the argument on the names which were assigned to send a message to the enemies which contained superiority status, danger, progress, and intimidating slogans with an intention to address the journey and strenght that King Mzilikazi and his nation had acquired.
Umsebenzi owethulwa ukufeza izidingo zeqhuzu le-“Master of Arts”, emnyangweni wezilimi zase-Afrika eYunivesithi yaseWitswatersraand